Identifying Coach and Institutional Characteristics That Facilitate the Development of NCAA Wheelchair Basketball Programs - Rutland, Emily A.; Suttiratana, Sakinah C.; Huang, Patrick; Ayala, Kimberly E. Ona; McGinniss, Kevin T.; Tuakli-Wosornu, Yetsa A. (Sports Innovation Journal, 2022)
Background: Despite national and institutional policies, American colleges do not currently provide student-athletes with disabilities equal access to sports opportunities. Disabled youth who wish to pursue their academic and athletic dreams in college thus have prohibitively limited options, even with popular American sports such as basketball. Purpose: The purpose of this study was to identify characteristics and factors that may facilitate the development and perpetuation of collegiate wheelchair basketball programs in the United States. Methods: Five qualitative interviews were conducted with coaches and/or program administrators of established college wheelchair basketball programs. Interviews were coded and analyzed to explore common themes. Results: Thematic data analysis uncovered five common themes important to the development and maintenance of these programs: a) coach characteristics, b) actions to recognize and address equity, c) boosters, d) institutional barriers, and e) network effects. Conclusion: These common factors are important in the development, sustainability, and longevity of college wheelchair basketball programs and should be considered by those interested in starting similar programs.
Keywords: Collegiate Sports; NCAA Sports; Para Sport; Wheelchair Basketball; adaptive sports; dept.rec; peer-reviewed